Can Capital-Skill Complementarity Explain the Rising Skill Premium in Developing Countries? Evidence from Peru in the 1990s - Mazumdar (†), Joy (2019)
The unsettled discussion continues about the factors behind the increase in the relative wages of skilled workers in developing countries. Using data from Peru for the years 1994 to 2000, we analyze the determinants of within-industry share of skilled workers. We use a translog cost function for gross output and are therefore able to incorporate the effects of materials, both domestic and imported, in addition to capital. We find that capital accumulation can explain a large fraction of the increase in the wage bill share and relative wages of skilled labor. This finding is contrary to the commonly held view that unobservable technological change is responsible for the rising skill premium in both developing and developed economies. A test for separability indicates that a gross output cost function is the appropriate one to use, and therefore share equations based on value-added cost functions could be misspecified.